Eminescu-teatralul: fascinația pentru scenă - PILCHIN, Maria (BIBLIOPOLIS, 2025)
Mihai Eminescu was attracted to the world of theater since his youth. According to Zoe Dumitrescu-Bușulenga, the influence of Shakespeare, as a total dramatist, on Eminescu was manifested early on, due to the contact with theater groups from abroad. This fascination with the stage led him to write about theatre, actors and spectators. Eminescu had an intense publicist activity, signing theatrical chronicles in Curierul de Iași and Timpul, where he stood out through an applied analysis and a lot of irony. His theatrical criticism, although harsh on the acting or the audience, praised the creators who brought the new and good quality art. In his chronicles, Eminescu showed a special concern for stage language and appreciated professional actors who could save a mediocre literary text. His critical analyzes of performances, audiences and theater groups reflect a complex vision of the Romanian theatrical phenomenon.